Pisces-RF: A helicon-plasma based linear-device for the study of fusion relevant plasma-materials-interactions - M.J. Baldwin; D. Nishijima; M.I. Patino; G. Gunner; T. Lynch; F. Chang; M.J. Simmonds; A. Založnik; S. Moore; B. Schwendeman; R. Ciamacco; R.P. Doerner; et al. (Nuclear Materials and Energy, 2023)
The helicon-plasma based-linear plasma-materials-interaction device, Pisces-RF is introduced. Steady-state plasma parameters in the target region are electron density up to ∼1019 m−3, electron temperature up to ∼10 eV, and ion flux up to ∼1023 m−2s−1 in D2 and He, with an associated maximum peak target heat flux of ∼1 MWm−2 and a few MWm−2 when accelerating ions with an electrical bias. Attached and detached target plasma regimes with both gaseous species can be achieved, as characterized by high and low Te (<1eV) plasmas with high fractions of singly ionized atomic ions. The downstream target plasma is inferred to have a low concentration of condensing or sticking impurity ions (< 0.1 ppb), as confirmed by accumulation experiments on electrically-floating targets in deposition-dominated low Te plasma conditions. The validation of Pisces-RF target PMI on W is confirmed by the observation of D retention values and W fuzz-layer thicknesses, obtained in D2 and He plasmas, that are in good agreement with prior literature. Lastly, the integration of Pisces-RF with a tandem ion-accelerator, to study the synergistic effects of simultaneous displacement damage and plasma irradiation, which we refer to as burning-plasma-material-interaction (BPMI), is discussed.